Conscience and community : Sterling M. McMurrin, Obert C. Tanner, and Lowell L. Bennion - Goldberg, Robert Alan, 1949-; Newell, L. Jackson, 1938-; Newell, Linda King (Salt Lake City : The University of Utah Press, 2017)
"Lowell Bennion, Sterling McMurrin, and Obert Tanner were friends and colleagues whose lives often intertwined. Professors at the University of Utah, these three scholars collaborated in addressing issues and events of their time; each influenced the thought and culture of Mormonism, helping to institute a new period of intellectual life and social activism. In Conscience and Community multiple scholars, family members, and others look at the private and public aspects of three lives and examine the roles they played in shaping their communities inside and out of their university and church. Lowell Bennion was founding director of the LDS Institute of Religion and professor of sociology at the University of Utah. He established multiple community service entities. Sterling McMurrin was a distinguished professor of philosophy and history, a graduate school dean, and former commissioner of education under JFK. He dismissed dogma and doctrine as barriers to a search for moral and spiritual understanding. Obert Tanner, also of the university's Philosophy Department, excelled in teaching and in business and became especially well known for philanthropy. The lives and work of these three men reveal the tensions between faith and reason, conscience and obedience. Their stories speak to us today because their concerns remain our concerns: racial justice, women's equality, gay rights, and the meaning of integrity and conscience"--Provided by publisher.
The LDS intellectual tradition : a study on three lives / Kathleen Flake -- The essential McMurrin : formation of character and courage / L. Jackson Newell -- The "old orthodoxy" : Sterling McMurrin and the development of Mormon thought / Brian D. Birch -- Fertile ground and fruitful harvests : McMurrin in Arizona and Washington, D.C. / J. Boyer Jarvis -- The spiritual quest of Obert C. Tanner / Robert Alan Goldberg -- Obert Tanner and the idea of a university / Mark Matheson -- Obert C. Tanner's Mormonism : the O.C. Tanner Company as a window into his soul / Kent Murdock -- Lowell Bennion and the things that matter most / Mary Lythgoe Bradford -- Lowell Bennion, race, and justice / Gregory A. Prince -- Lowell, a teacher by heart / Emma Lou Warner Thayne -- Public men and the challenge of their private worlds : a conversation / Linda King Newell with Carolyn Tanner Irish, William McMurrin, Ellen Bennion Stone -- Summing up : poised fortuitously in place and time / L. Jackson Newell.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Added to collection customer.56279.3 - Master record variable field(s) change: 072
Keywords: McMurrin, Sterling M. -- Influence; Tanner, Obert C. -- 1904-1993 -- Influence; Bennion, Lowell L., -- 1908-1996 -- Influence; Church of Jesus Christ of Latter-day Saints -- Doctrines; Bennion, Lowell L., -- 1908-1996.; McMurrin, Sterling M; Tanner, Obert C. -- 1904-1993.; Church of Jesus Christ of Latter-day Saints; Mormon Church -- Doctrines; Influence (Literary, artistic, etc.); Mormon Church -- Doctrines; Theology, Doctrinal; RELIGION / Christianity / Denominations; Electronic books